The Role of female combatants in the Nicaraguan revolution and counter revolutionary war - García, Martín Meráz, author.
1 online resource.
Keywords: The revolution in Nicaragua was unique in that a large percentage of the combatants were women. The Role of Female Combatants in the Nicaraguan Revolution and Counter Revolutionary War is a study of these women and those who fought in the Contra counter revolution on the Atlantic Coast. This book is a qualitative study based on 85 interviews with female ex-combatants in the revolution and counter revolution from the 1960s to the end of the 1980s, as well as field observations in Nicaragua and the autonomous regions of the Atlantic Coast. It explores the reasons why women fought, the sacrifices they made, their treatment by male combatants, and their insights into the impact of the revolution and counter-revolution on today's Nicaragua. The analytical approach draws from political psychology, social identity dynamics such as nationalism and indigenous identities, and the role of liberation theology in the willingness of the female revolutionaries to risk their lives. Researchers and students of Gender Studies, Latin American and Latino Studies, and Political History will find this an illuminating account of the Nicaraguan Revolution and counter revolution, which until now has been rarely shared.